2016
DOI: 10.2135/cropsci2015.09.0565
|View full text |Cite
|
Sign up to set email alerts
|

Plant Population Influence on Maize Yield Components in Croatia and Nebraska

Abstract: Analysis of yield components to address inconsistent maize (Zea mays L.) grain yields across plant populations is limited in Europe and the United States. The research objectives were to compare maize yield components at low and high plant populations in eastern Nebraska and central Croatia using path analysis to better understand maize grain yield determination with changing plant population and determine relative importance among maize primary and secondary yield components. Research was conducted by plantin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
30
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 28 publications
6
30
3
1
Order By: Relevance
“…Pearson correlations were calculated to identify interrelationships among measured parameters, and path correlation analysis (Agrama 1996;Mohammadi et al 2003) of yield and the primary and secondary yield components was completed using PROC CALIS to determine model goodness-of-fit. PP responses from this study have been reported previously in Milander et al (2016), while this article reports the hybrid maturity effects on maize yield and components.…”
Section: Cereal Research Communicationssupporting
confidence: 72%
See 1 more Smart Citation
“…Pearson correlations were calculated to identify interrelationships among measured parameters, and path correlation analysis (Agrama 1996;Mohammadi et al 2003) of yield and the primary and secondary yield components was completed using PROC CALIS to determine model goodness-of-fit. PP responses from this study have been reported previously in Milander et al (2016), while this article reports the hybrid maturity effects on maize yield and components.…”
Section: Cereal Research Communicationssupporting
confidence: 72%
“…Maize hybrid yield response to increasing PP above 60,000 ± 3000 plants ha -1 is inconsistent across locations, soil types, and hybrids (Reeves and Cox 2013;Milander et al 2016). Maize hybrid yield often follow quadratic (Novacek et al 2013(Novacek et al , 2014 or quadratic-plateau models (Hammer et al 2009).…”
Section: Cereal Research Communicationsmentioning
confidence: 99%
“…However, most other yield components are defined at a later stage in plant development, that is, the ear size and grain size are determined by the V12 and R2‐R3 stage, respectively, and therefore they could be affected by environmental factors, such as intraspecific competition caused by a higher number of plants per area. Our results are in agreement with most recent studies that have shown a linear decrease in the number of ears per plant, kernel length and weight, and ear length in response to an increase in plant population in maize (Xu et al, 2017a; Milander et al, 2016; Qian et al, 2016; Testa et al, 2016; Haegele et al, 2014; Hernández et al, 2014; Van Roekel and Coulter, 2012; Kappes et al, 2011). However, we found no plant population effect for the kernel weight in the winter season.…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies have shown that under high planting densities, more attention should be paid to changes in photosynthetic characteristics associated with canopy structure and that improvements in the yield of maize crops should be promoted through the development of cultivation and management coordination groups and individuals (Sarlangue et al, 2007; Niu et al, 2013). Therefore, optimum population structure is essential for high yield under high density conditions (Maddonni et al, 2001; Milander et al, 2016). Mixed cropping enhanced the complementarity between plant types and populations, improved the population canopy structure, and increased use of the space and natural resources (Daellenbach et al, 2005; Wei et al, 2011).…”
mentioning
confidence: 99%